1986
DOI: 10.1111/j.1755-3768.1986.tb06911.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated argon laser trabeculoplasty

Abstract: In 20 eyes (18 patients) with simple or capsular glaucoma in which a first full-circumference argon laser trabeculoplasty resulted in early or late failure, laser trabeculoplasty was repeated. In 12 eyes the second trabeculoplasty was clinically successful. At an average follow-up time of 30 months after second trabeculoplasty, the treatment was still successful in six patients. Early failure after the first treatment seems to be unfavourable for the outcome of secondary treatment. No correlation was found bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…These results are comparable to three previous reports of repeat ALT (Starita et al 1984;Bergea 1986;Grayson et al 1988), although others found it to be less successful (Brown et al 1985;Messner et al 1987;Richter et al 1987). A prospective study of argon laser trabeculoplasty (Fink et al 1988) also recorded a low success rate when ALT was performed.…”
Section: Discussionsupporting
confidence: 92%
“…These results are comparable to three previous reports of repeat ALT (Starita et al 1984;Bergea 1986;Grayson et al 1988), although others found it to be less successful (Brown et al 1985;Messner et al 1987;Richter et al 1987). A prospective study of argon laser trabeculoplasty (Fink et al 1988) also recorded a low success rate when ALT was performed.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 46 eyes that were classified as failures at the end of the 24-month follow-up period, three were able to withstand intensified medical treatment at that time, 16 received secondary ALT (Bergei 1986) and eight, mainly among cases of early failure with high IOP, underwent a filtering operation as a first additive treatment. In the other 19 failures the IOP level was accepted without change in therapy as the pressure reduction was nevertheless considerable and perimetry did not reveal any further loss of function.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, repeat ALT sometimes produced paradoxical IOP elevations (presumably because of cumulative coagulative damage to the trabecular outflow pathway 61 ) that often required surgical intervention. [62][63][64][65][66][67] On this basis, repeat ALT was not incorporated into the Glaucoma Laser Trial study design: when additional IOP reduction was required in laser-first eyes, medical therapy was initiated. 68 SLT uses the Q-switched, frequency-doubled Nd:YAG laser platform and consists of ∼100 contiguous nonoverlapping treatment spots over the full 360 degrees of TM.…”
Section: The Case For Low Energy Slt Standard Slt Causes Trabecular M...mentioning
confidence: 99%